AN EFFECT OF UNIVERSITY LEADER'S CONFIDENCE ON THE EFFECTIVENESS OF A UNIVERSITY - D. A. Endovitskiy; Yu. A. Bubnov; K. M. Gaidar (Moscow Polytechnic University, 2017)
The conditions of the traditional resources limitation compel the universities to improve their efficiency by means of transition from extensive to intensive development, i.e. by using the internal resources.The purpose of the article is the analysis of the situations when the effectiveness of a university is mostly determined by the socio-psychological determinants, such as personality of a University head, his (her) characteristics, experience, professional competence, and others. Using the method of logical-psychological analysis the authors have found the most favorable conditions for the University's effectiveness, when the rector - an official head is also recognized as a leader of a team and characterized by self-confidence as an essential quality of a leader. It is the most important «soft» competence which is relevant for a modern manager. The correlations between certain aspects of the University leader self-confidence and some university resources are revealed. It is concluded that the leadership capacity of the University head is a basic inner resource for University's effective and stable movement forward. The paper formulates the proposals improve the mechanism of nomination of candidates for position passing interview and examination at the Attestation Commission under the Ministry of education and science of the Russian Federation.